Role of the Arabidopsis RING-H2 Protein RBX1 in RUB Modification and SCF Function - Gray, William M. (American Society of Plant Biologists, 2002)
The ubiquitin-related protein RUB/Nedd8 is conjugated to members of the cullin family of proteins in plants, animals, and fungi. In Arabidopsis, the RUB conjugation pathway consists of a heterodimeric E1 (AXR1-ECR1) and a RUB-E2 called RCE1. The cullin CUL1 is a subunit in SCF-type ubiquitin protein ligases (E3s), including the SCF(TIR1) complex, which is required for response to the plant hormone auxin. Our previous studies showed that conjugation of RUB to CUL1 is required for normal SCF(TIR1) function. The RING-H2 finger protein RBX1 is a subunit of SCF complexes in fungi and animals. The function of RBX1 is to bind the ubiquitin-conjugating enzyme E2 and bring it into close proximity with the E3 substrate. We have identified two Arabidopsis genes encoding RING-H2 proteins related to human RBX1. Studies of one of these proteins indicate that, as in animals and fungi, Arabidopsis RBX1 is an SCF subunit. Reduced RBX1 levels result in severe defects in growth and development. Overexpression of RBX1 increases RUB modification of CUL1. This effect is associated with reduced auxin response and severe growth defects similar to those observed in axr1 mutants. As in the axr1 mutants, RBX1 overexpression stabilizes the SCF(TIR1) substrate AXR2/IAA7. The RBX1 protein is a component of SCF complexes in Arabidopsis. In addition to its direct role in SCF E3 ligase activity, RBX1 promotes the RUB modification of CUL1 and probably functions as an E3 ligase in the RUB pathway. Hypermodification of CUL1 disrupts SCF(TIR1) function, suggesting that cycles of RUB conjugation and removal are important for SCF activity.